International banking and nonbank financial intermediation: Global liquidity, regulation, and implications - Claudia M. Buch; Linda S. Goldberg (Federal Reserve Bank of New York, 2024)
Global liquidity flows are largely channeled through banks and nonbank financial institutions. The common drivers of global liquidity flows include monetary policy in advanced economies and risk conditions. At the same time, the sensitivities of liquidity flows to changes in these drivers differ across institutions and have been evolving over time. Microprudential regulation of banks plays a role, influencing leverage and capitalization, changing sensitivities to shocks, and also driving risk migration from banks to nonbank financial institutions. Risk sensitivities and flightiness of global liquidity are now strongest in more leveraged nonbank financial institutions, raising challenges in stress episodes. Current policy initiatives target linkages across different types of financial institutions and associated risks. Meanwhile, significant gaps remain. This paper concludes by discussing policy options for addressing systemic risk in banks and nonbanks.
Keywords: F3; G21; G23; G28; 330; international bank; nonbank financial institution; global liquidity; regulation; prudential policy